Interviewer- vs. Self-administration of PROMIS Measures for Adults with Traumatic Injury - Kisala, Pamela A. (Health Psychol, 2019)
OBJECTIVE: To assess differential item functioning (DIF) and observed mean differences across two modes of administration for PROMIS measure scores in a sample of adults with traumatic injury. METHODS: Items from 7 PROMIS adult measures (v1.0 Physical Function, Fatigue, Pain Interference, Anger, Anxiety, and Depression and v2.0 Social Health - Emotional Support) were administered as fixed-length short forms in random order to a cross-sectional sample. Participants were randomly assigned to interviewer- administered (phone or in-person) or self-administered (via Assessment Center(SM) website) conditions. The research was conducted at five medical rehabilitation institutions across the U.S. Participants included 277 adults with spinal cord injury (SCI; n = 148) or traumatic brain injury (TBI; n = 129). RESULTS: DIF analyses indicated that all items were invariant to mode of administration. There was no significant effect of mode of administration for the majority of PROMIS measures tested. Regarding observed scores, there were small but significant effects of mode of administration on the Emotional Support and Depression measures, with participants in the interview condition reporting better support/fewer symptoms. CONCLUSIONS: PROMIS instruments demonstrated measurement equivalence across interviewer- administered and self-administered conditions. These findings are particularly important for research or clinical applications where administration of PROMIS measures by independent, web- or tablet-based administration is not ideal, for example with individuals with physical or cognitive disabilities or with individuals who lack computer and/or internet access. PROMIS v1.0 Depression and PROMIS v2.0 Emotional Support scores displayed a tendency towards social desirability which should be considered when these measures are interviewer- administered.